2013
DOI: 10.1186/2052-1847-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, knee osteoarthritis and knee arthroplasty: a review

Abstract: The incidence of obesity is rising worldwide. Obesity is a risk factor for developing osteoarthritis in the knee. Obesity and knee osteoarthritis are independently disabling conditions and in combination pose difficult therapeutic challenges. This review will discuss obesity, osteoarthritis, and the problems associated with knee osteoarthritis in an obese population. Treatment options including surgery and its success will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 50 publications
1
41
0
3
Order By: Relevance
“…40 While not all studies agree, 41 data has demonstrated an increased rate of peri-operative complication in obese patients and an increased risk of premature joint failure and revision. 42 The majority of patients in our study were classified as obese. Arthokinex TM (ACS) effectively alleviated symptoms in obese patients and could facilitate cartilage repair as well as potentially provide peri-operative benefits if surgery is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…40 While not all studies agree, 41 data has demonstrated an increased rate of peri-operative complication in obese patients and an increased risk of premature joint failure and revision. 42 The majority of patients in our study were classified as obese. Arthokinex TM (ACS) effectively alleviated symptoms in obese patients and could facilitate cartilage repair as well as potentially provide peri-operative benefits if surgery is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, obesity is an independently recognized modifiable risk factor for the development and progression of osteoarthritis (OA). 3,4 Compared with normal weight patients, obese patients have a 3-fold to 5-fold increased risk of developing knee OA. 5,6 It is thought that increased body mass results in increased forces across a joint, thus progressing 7 OA.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity contributes to a host of significant chronic medical problems, with increased rates of diabetes mellitus [4][5][6][7][8], cardiovascular disease [4,6,7,[9][10][11][12], hypertension [4,6,[13][14][15], hyperlipidemia [4][5][6][7]10,13,15,16], obstructive sleep apnea [4,6], cerebrovascular disease [4,7,9,15,17,18] and gall bladder disease [4,16,19] among others. Additionally, obesity has been widely recognized as a risk factor for the development of osteoarthritis, with the knee being one of the most commonly affected joints [20,21]. A systematic review and meta-analysis assessing the relationship between BMI and knee osteoarthritis demonstrated a nearly three-fold increased risk of developing osteoarthritis of the knee in patients who are overweight or obese compared to normal weight patients [22].…”
mentioning
confidence: 99%